On interior regularity of solutions of a class of almost-hypoelliptic equations - Hayk Ghazaryan; Vachagan Margaryan (National Academy of Sciences of Armenia)
In this paper it is proved that all distributional solutions of the non-degenerate, almost hypoelliptic (hypoelliptic by the one of variables) equation $P(D)u = P(D_{1},D_{2})u = 0$ are infinitely differentiable in the certain strip in $E^{2}$ under a priori assumption that they and its certain derivatives are square integrable with a certain exponential weight.
Keywords: Partial differential equations; Field theory and polynomials